2012
DOI: 10.1155/2012/463909
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Neurodegeneration and Memory Loss in Down Syndrome

Abstract: Down syndrome (DS) is a condition where a complete or segmental chromosome 21 trisomy causes variable intellectual disability, and progressive memory loss and neurodegeneration with age. Many research groups have examined development of the brain in DS individuals, but studies on age-related changes should also be considered, with the increased lifespan observed in DS. DS leads to pathological hallmarks of Alzheimer's disease (AD) by 40 or 50 years of age. Progressive age-related memory deficits occurring in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 132 publications
(156 reference statements)
6
40
0
2
Order By: Relevance
“…Individuals with DS concurrently display enhanced microglial activation (Head et al 2016; Wilcock and Griffin 2013; Wilcock et al 2015), elevated oxidative stress, and mitochondrial dysfunction (Pagano and Castello 2012; Perluigi and Butterfield 2012). Collectively, these pathological hallmarks forge a pathway to AD in people with DS (DS-AD) leading to widespread and progressive neurodegeneration of basal forebrain cholinergic neurons (BFCNs), locus coeruleus (LC) noradrenergic (NE) neurons, certain hippocampal neuronal populations (Lockrow et al 2012; Millan Sanchez et al 2012; Salehi et al 2009), and neurons in certain cortical areas (Sadowski et al 1999; Teipel et al 2004), similar to the neurodegeneration observed in idiopathic AD (Wisniewski et al 1985). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with DS concurrently display enhanced microglial activation (Head et al 2016; Wilcock and Griffin 2013; Wilcock et al 2015), elevated oxidative stress, and mitochondrial dysfunction (Pagano and Castello 2012; Perluigi and Butterfield 2012). Collectively, these pathological hallmarks forge a pathway to AD in people with DS (DS-AD) leading to widespread and progressive neurodegeneration of basal forebrain cholinergic neurons (BFCNs), locus coeruleus (LC) noradrenergic (NE) neurons, certain hippocampal neuronal populations (Lockrow et al 2012; Millan Sanchez et al 2012; Salehi et al 2009), and neurons in certain cortical areas (Sadowski et al 1999; Teipel et al 2004), similar to the neurodegeneration observed in idiopathic AD (Wisniewski et al 1985). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, oxidative stress is a major etiological factor on the pathway to DS-AD (Pagano and Castello 2012). The superoxide dismutase 1 ( SOD1 ) gene is encoded on Hsa21, within the so called Down syndrome critical region (DSCR) (Antonarakis 1998) and has been shown to have up to 50% increased activity in all DS tissues examined, including the brain (Sinet 1992), as well as in DS mouse models (Lockrow et al 2012). The levels of SOD1 protein and mRNA are particularly high in hippocampal pyramidal neurons in DS, which are especially susceptible to the degenerative processes that occur in DS-AD (Furuta et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the Ts65Dn (TS) model carries trisomic segments of mouse chromosome 16 that contain regions orthologous to human chromosome 21, and share some DS-relevant behavioral and morphological features (11,12). The TS model has been widely used for the study of age-related neurodegeneration and cognitive impairments parallel to those seen in the brain of DS individuals (13, 14). These mice exhibit memory and learning deficits associated with progressive loss of basal forebrain cholinergic neurons (1517) and reduced hippocampal long-term potentiation (LTP) and increased long-term depression (LTD) (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Research on this topic may be of great interest since oxidative damage has been proposed as a pathogenic mechanism of atherosclerosis, cell ageing, neurodegeneration [2], carcinogenic events and immunological disorders in this population [3]. Oxidative stress is a term used to describe the effect of oxidation in which an abnormal level of reactive oxygen species, such as free radicals (e.g.…”
Section: Introductionmentioning
confidence: 99%